4th Mathematics, Informatics, Science and Education International Conference - Susiyawati, Enny (Journal of physics. Conference series, 2021)
The 4th Mathematics, Informatics, Science and Education International Conference was successfully held on October 3, 2020 at Universitas Negeri Surabaya, Surabaya, East Java, Indonesia. This conference was organized by Universitas Negeri Surabaya. The 4th MISEIC was the first conference in the history of MISEIC which was completely conducted using a digital platform in line with the social distancing norms due to the COVID-19 breakout. The theme for the 4th MISEIC was "Advancing Research on Mathematics, Informatics, Science and Education for Building a Better Society". Using the theme, the 4th MISEIC invited scientists, education experts, practitioners, and students through this scientific forum to share their ideas, research findings, and issues about theoretical and practical knowledge in Mathematics, Informatics, Science, and STEM education. Their shared ideas were expected to have important contributions for building "a better society", such as solving problems caused by, but not limited to, the pandemic situations. This year, MISEIC was held in the form of An International Joint Conference on Science, Technology, Art, and Humanities. The joint conference merged five Universitas Negeri Surabaya-organized conferences into one major event which was held on 3rd to 4th of October 2020. The joint conference included the 4th MISEIC, the 3rd International Conference on Vocation Education and Electrical Engineering (ICVEE), the 4th International Conference on Education Innovation (ICEI), the 2nd International Conference on Research and Academic Community Services (ICRACOS), and the 1st International Conference on Cultural Studies and Applied Linguistics (ICCSAL). The first day was dedicated to the conferences which have scopes focused on Science and Technology, namely MISEIC, ICVEE, and ICRACOS, whereas the second day represented Art and Humanities-focused conferences. In this joint conference, each individual conference was represented by one keynote and one or more speakers from overseas universities or institutions. However, the joint conference was organized only for the meeting day. Practically, each supporting conference had its own brochure, website, and article management system. The modification from an individual conference into the joint conference was conducted because of reallocation of academic budget to COVID-19 aids. The joint conference was completely conducted online using Zoom as a platform. Similar to offline form, the online joint conference included plenary and roundtable sessions. In the plenary session, each keynote speaker delivered a talk directly on the Zoom within 30 minutes. This session was also broadcasted live via an official YouTube channel of Universitas Negeri Surabaya. Each talk was followed by live Question and Answer (Q&A) for 15 minutes. Participants were offered to deliver their questions to each keynote speaker using oral or written forms on the Zoom or via live chat on YouTube. After one hour break, the roundtable sessions were conducted and organized by each individual supporting conference. For MISEIC, these roundtable sessions were preceded by a 20-minute live talk on the Zoom from an invited speaker. This session invited particularly all presenters and participants of the 4th MISEIC. The live Q&A for this forum was held using oral and written forms on the Zoom and lasted for 10 minutes. At the end of the session, each MISEIC presenter was assigned to a particular roundtable discussion room based on the ID shown in the Zoom. The committee provided 10 roundtable discussion rooms to accommodate all MISEIC's presenters. Each room consisted of one moderator, one IT technician, 8-9 presenters, and some participants. There were three sessions in each roundtable discussion room which lasted for 50 minutes for each session comprising of 25 minutes for presenters' video presentations and 25 minutes for live Q&A via Zoom. Preceding to the conference day, each MISEIC's presenter was required to submit a seven-minute video presentation to a link which was provided by the committee. The decision to use a video instead of a live presentation was taken in order to avoid delay during the presenters' presentation due to internet connection problems. List of Technical Program Committee, Conference Overview, Images are available in this pdf.